(untitled) (KYAMC Journal, 2018)
Background: Now a day’s obesity is a burden Worldwide. The Prevalence of obesity is increasing in both the developed and developing Countries. Objectives: To investigate lipid profile in obesity. Methods: This study was carried out in the Department of Physiology, Mymensing Medical College, Mymensing, Bangladesh during the period of January 2009 to December 2009. Lipid profile was measured in 150 cases of over weight and obese. Results: Serum total cholesterol, triacylglecerol, LDLcholesterol were high in obese group but HDL cholesterol was high in non-obese group. Conclusion: Obesity affects blood lipid & lipoprotein metabolism. KYAMC Journal Vol. 9, No.-3, October 2018, Page 115-119